The Development of China's Exports – Is There a Decoupling from the EU and the US? - Volker Brühl (Intereconomics, 2024)
Some observers warn that a high level of economic dependence on China could negatively affect the economic resilience of western economies and therefore recommend reducing such dependence by gradually decoupling from China. On the other hand, industry leaders emphasise the economic importance of China and warn against any kind of trade conflicts. Against this background, this article briefly analyses the development of China's export strategy. It finds that the export intensity of the Chinese economy is diminishing and that exports are becoming more diversified overall. In addition, the relative importance of the United States and the European Union as export markets has been reduced, indicating a gradual decoupling of China from western economies. Conversely, exports to China have become more important for both the EU and the US. Although the figures remain at a non- critical level, Europe's export activities could be more diversified as well.
Keywords: F01; F14; O1; O53; 330; Export; Export industry; China; EU countries; USA; Export; Exportwirtschaft; China; EU-Staaten; USA